ESTIMATION OF VARIANCE COMPONENTS AND HERITABILITY OF BIRTH WEIGHT THROUGH DIFFERENT METHODS IN SWEDISH RED AND WHITE CATTLE - V. Aksakal; B. Bayram; M. Yanar; O. Akbulut (Journal of Animal and Plant Sciences, 2012)
Data on 368 birth records of Swedish Red and White cattle herd raised organically at Dogan Organic Dairy Cattle Farm for a period of 2006 and 2009 (4 years) were used to estimate the effects of different environmental factors on birth weight. Additionally, a comparison of four methods for variance component estimation to compute heritability of birth weight was performed using ML (Maximum likelihood), MINQUE (Minimum variance quadratic unbiased estimation), REML (Restricted maximum likelihood) and Henderson’s Method III. Average abortion rate, stillbirth rate, twin and single birth rates of Swedish Red and White cattle were as 4.5%, 4.3%, 3.2% and 87.7% respectively. The least squares mean for birth weight was 37.4±0.70 kg. While effects of calving year (P<0.01), calving season (P<0.05) and sex of calve (P<0.01) were significant, and the effect of age of dam was not significant (P>0.05). Sire and error variance components and standard error of the heritability obtained by using ML method were lower than those obtained by the other three methods. Heritability estimates for birth weight obtained by ML, REML, MINQUE and Henderson Method III were 0.57±0.22, 0.62±0.24, 0.65±0.25 and 0.59±0.24, respectively. It is concluded that the ML procedure was superior for estimating variance components and heritability of birth weight of Swedish Red and White cattle and non-genetic factors influencing the birth weight should also be considered in selection and an adjustment for the significant environmental factors should be made.
Keywords: Swedish Red and White cattle; birth weight; variance components; heritability; organic dairy farming